The slope of a line is defined as:
m = (change in y) / (change in x)
or:
m = (y2 - y1) / (x2 - x1)
Given the points (-3, 3) and (0,-3) means:
x1 = -3
x2 = 0
y1 = 3
y2 = -3
Plugging these numbers into the equation for m yields:
m = (-3 - 3) / (0 - -3)
m = (-3 - 3) / (0 + 3)
m = (-6) / (3)
m = -2
Note that a slope of 0 means that there is no change in y, or that y1 = y2
2006-11-08 09:20:00
·
answer #1
·
answered by dmncrvn007 2
·
1⤊
0⤋
The equation for the slope is y = mx + b where b= "y" intercept
and m=slope. The "y" intercept is the point at which the line crosses the "y" axis or a value of x=0 (this is one of the given points. Substituting into the equation:
3 = m (-3) + (-3)
solving for m:
m= [3 - (-3) ] / -3
m = 6 / -3
m = -2 (this is the slope of the line)
You can also, very easily calculate the slope by calculating the ratio of the change in "y" / change in "x" or
3- (-3) / (0-3) or 6 / -3 = -2 calculating the other direction you get the same answer:
-3-3 / 3-0 or -6 / 3 - -2
2006-11-08 09:33:31
·
answer #2
·
answered by Doug R 5
·
0⤊
0⤋
Slope is change in y divided by change in x:
(-3-3)/(0-(-3)) = -6/3 = -2. Draw a sketch to see it!
The line segment goes down 6 units and over 3 units on the sketch.
2006-11-08 09:17:30
·
answer #3
·
answered by modulo_function 7
·
1⤊
0⤋
Slope = rise/run = change in Y / change in X
3 - (-3) / -3 - 0 = 6/(-3) = -2
2006-11-08 09:16:42
·
answer #4
·
answered by Will 4
·
1⤊
0⤋
U could find the gradient
rise\run which is y2 - y1\x2 - x1
so therefore plug it into the formula and u get -3 - 3\0 - [-3]
So ur answer wud be -2
2006-11-08 09:18:18
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
-3-(3)
_____ = -6/3= -2 ( -2 is the answers)
0-(-3)
2006-11-08 09:22:46
·
answer #6
·
answered by J 6
·
0⤊
0⤋
cant be zero. zero means horizontal line, where by the y-coordinates will be the same.
hmm..try the formula (y-y')/(x-x')
so [3- (-3)] / -3 - 0
= -2
Hope this helps=)
apl
2006-11-08 09:18:38
·
answer #7
·
answered by luv_phy 3
·
0⤊
0⤋
slope = Îy/Îx
slope = (y2 - y1)/(x2 - x1)
slope = (-3 - 3)/(0 - -3)
slope = (-6)/(3)
slope = -2
2006-11-08 09:16:21
·
answer #8
·
answered by عبد الله (ドラゴン) 5
·
1⤊
0⤋